(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Purpose – With the growing importance of consumer interaction on web and social media platforms, consumer engagement has been extensively examined for various brands but not for online food community platforms. To mitigate this gap in the literature, the current study is undertaken to identify the factors that impact the customer engagement model for an online food community platform. The study also discusses the drivers of the customer engagement model and its outcomes for an online food community platform. To investigate how well these online food communities, engage with customers, the study examines the constructs i.e. community active participation, brand engagement and community trust. Design/methodology/approach – A questionnaire-based survey is conducted with the online food community members to gather data. Exploratory factor analysis followed by confirmatory factor analysis has been applied to analyse the data. Findings – The study identifies the role and significance of encouraging active participation in engaging customers in an online food community context. Further, it also recognizes community trust to be a key factor in consumer brand engagement. Research limitations/implications – The study presents understanding to the marketers in terms of managing customer engagement with their online food communities. Originality/value – There are numerous views among researchers regarding the customer engagement. Only limited studies have focussed on this construct in the perspective of markets in developing economies. No previous study is done on studying customer engagement in an online food community platform. Thus, the study attempts to close this gap.